Implementation of the Minister of Religious Affairs Regulation No. 20 of 2019 on Marriage Registration Among Muslims in Simpang Kanan District, Aceh Singkil Regency - Mahdi, Zarman; Tanjung, Dhiauddin; Hafsah, Hafsah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study examines the implementation of the Minister of Religious Affairs Regulation No. 20 of 2019, focusing on marriage registration among the Muslim community in Simpang Kanan Subdistrict, Aceh Singkil Regency. The regulation mandates a minimum age of 19 years for both brides and grooms. However, challenges persist, particularly regarding young marriages and the community's understanding of marriage registration requirements. Utilizing a qualitative approach, including observation, documentation, and interviews, this research reveals that while the regulation has been generally applied, some provisions remain inadequately implemented. Key issues include incomplete documentation by prospective couples and a lack of awareness regarding the regulation's Article 7, which leads to the rejection of marriage registration in cases of administrative errors. The study suggests that the Office of Religious Affairs should enhance its socialization efforts and collaborate more closely with local authorities to ensure the proper application of the regulation and the accuracy of population data. These findings underscore the need for continued efforts to improve the understanding and implementation of marriage regulations in the region.